1993
DOI: 10.1002/1097-0142(19931015)72:8<2433::aid-cncr2820720822>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Serum and ascitic fluid levels of interleukin-1, interleukin-6, and tumor necrosis factor-alpha in patients with ovarian epithelial cancer

Abstract: Background. Recent studies have shown that multiple cytokines are secreted by ovarian epithelial cancer cells. Previous studies have shown that the cancer cell lines secrete macrophage colony‐stimulating factor (M‐CSF), granulocyte–macrophage colony‐stimulating factor (GM‐CSF), interleukin‐1 (IL‐1), interleukin‐6 (IL‐6), and transforming growth factor‐alpha (TGF‐α). Concomitantly, the serum levels of one of the growth factors (M‐CSF) was found to be significantly elevated in patients with primary ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 20 publications
4
63
1
4
Order By: Relevance
“…The data presented here confirm a statistically significant difference in VCAM-1 protein expression on the surface of mesothelial cells from patients with ovarian cancer compared with cancer-free women. Whereas the mechanisms that regulate VCAM-1 expression in ovarian cancer patients are unknown, a known inducer of VCAM-1 expression, TNFa, is expressed by ovarian cancer cells (25) and found in malignant ascites (26). However, VCAM-1 expression was observed in patients without evidence of peritoneal metastasis (i.e., stage I or II ovarian cancer) and in regions lacking ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here confirm a statistically significant difference in VCAM-1 protein expression on the surface of mesothelial cells from patients with ovarian cancer compared with cancer-free women. Whereas the mechanisms that regulate VCAM-1 expression in ovarian cancer patients are unknown, a known inducer of VCAM-1 expression, TNFa, is expressed by ovarian cancer cells (25) and found in malignant ascites (26). However, VCAM-1 expression was observed in patients without evidence of peritoneal metastasis (i.e., stage I or II ovarian cancer) and in regions lacking ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In human ovarian cancer cells, IL6 signaling was shown to regulate proliferation, adhesion, and invasion (10), and the autocrine production of TNFa stimulated the growth of ovarian cancer cell lines (11). Previous case-control studies have observed significantly higher circulating levels of these inflammatory markers in ovarian cancer cases compared with healthy controls (12,13). However, due to possible reverse causation bias, the causal roles of these markers in ovarian carcinogenesis cannot be established from retrospective studies, and these markers could be just indicators of a host response to the neoplastic process.…”
Section: Introductionmentioning
confidence: 98%
“…Extreme elevations in IL-6 levels have been reported in the ascitic fluid, 8,12,29,30 and ovarian tumor cells in vitro produce substantial amounts of IL-6. 8,29 However, the extent to which the level of IL-6 in the peripheral blood reflects IL-6 in the area of the tumor is still unknown.…”
mentioning
confidence: 98%